Fracture Shape and Orientation Contributions to P-Wave Velocity and Anisotropy of Alpine Fault Mylonites - Charoensawan, Jirapat; Adam, Ludmila; Ofman, Michael; Toy, Virginia; Simpson, Jonathan; Zhong, Xin; Schuck, Bernhard (Frontiers in Earth Science, 2021)
P-wave anisotropy is significant in the mylonitic Alpine Fault shear zone. Mineral- and texture-induced anisotropy are dominant in these rocks but further complicated by the presence of fractures. Electron back-scattered diffraction and synchrotron X-ray microtomography (micro-CT) data are acquired on exhumed schist, protomylonite, mylonite and ultramylonite samples to quantify mineral phases, crystal preferred orientations, microfractures and porosity. The samples are composed of quartz, plagioclase, mica and accessory garnet, and contain 3-5% porosity. Based on the micro-CT data, the representative pore shape has an aspect ratio of 5:2:1. Two numerical models are compared to calculate the velocity of fractured rocks: a 2D wave propagation model, and a differential effective medium model (3D). The results from both models have comparable pore-free fast and slow velocities of 6.5 km/s and 5.5 km/s, respectively. Introducing 5% fractures with 5:2:1 aspect ratio, oriented with the longest axes parallel to foliation decreases these velocities to 6.3 km/s and 5.0 km/s, respectively. Adding both randomly oriented and foliation-parallel fractures hinders the anisotropy increase with fracture volume. The dominant porosity-free, mica-dominated anisotropy becomes independent of porosity when 80% of fractures are randomly oriented. Modeled anisotropy in 2D and 3D are different for similar fracture aspect ratios, being 30% and 15%, respectively. This discrepancy is the result of the underlying assumptions and limitations. Our numerical results explain the effects that fracture orientations and shapes have on previously published field- and laboratory-based studies. Through this numerical study, we show how mica-dominated, pore-free P-wave anisotropy compares to that of fracture volume, shape and orientation for protolith and shear zone rocks of the Alpine Fault.